Fiqh Muamalah-Based Buy and Sell Transactions: Their Relevance and Impact on the Islamic Economy - Faridatun Najiyah; Ayu Maretta Maharani (Journal of Economics and Social Sciences (JESS), 2025)
This article discusses the concept of buying and selling from the perspective of Islamic jurisprudence and its impact on the development of the Sharia economy. Buying and selling is one of the most common economic activities and has a strong legal basis in Islamic jurisprudence, which emphasizes the principles of justice, openness, and certainty in trade interactions. This study discusses various types of transactions that are permitted and prohibited according to Sharia law, and outlines the pillars and validity in the practice of buying and selling. Using a normative analysis approach and case studies, this article also examines how the implementation of the principles of Islamic jurisprudence can contribute to Sharia-based economic growth. Among them, transactions in accordance with Sharia provisions are considered capable of increasing public trust in business activities, encouraging the development of the small business sector, and supporting the distribution of business, encouraging the development of the small business sector, and supporting the distribution of economic welfare.